2018
DOI: 10.1039/c7tc03457a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CdSe and CdSe/CdS nanocrystals on the optical activity of chiral organic molecules

Abstract: Influence of semiconductor nanocrystal diameter and shell thickness on optical activity of chiral organic molecule is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Similar results were also obtained by Martynenko et al [68]. This model is often used to explain a wide range of observed phenomena including influence of QD size [62], shell thickness [62,69], nature and binding mode of ligands [70][71][72][73][74] on the position, shape and intensity of CD peaks, as well as the influence of QDs on the properties of chiral molecules [75], which will be discussed in the present review. In addition, this method allows the investigation of the QD energy structure using CD spectra [68].…”
Section: The Mechanisms Of Ligand-induced Chirality In Qdssupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results were also obtained by Martynenko et al [68]. This model is often used to explain a wide range of observed phenomena including influence of QD size [62], shell thickness [62,69], nature and binding mode of ligands [70][71][72][73][74] on the position, shape and intensity of CD peaks, as well as the influence of QDs on the properties of chiral molecules [75], which will be discussed in the present review. In addition, this method allows the investigation of the QD energy structure using CD spectra [68].…”
Section: The Mechanisms Of Ligand-induced Chirality In Qdssupporting
confidence: 84%
“…Moreover, it has been theoretically predicted by Govorov et al [88][89][90] that a nonchiral planar molecule can become optically active when it forms a complex and couples via dipole and multipole Coulomb interactions with achiral NCs. In another important piece, it has also been demonstrated that CD signal intensity of the chiral molecule chlorine e6 can be significantly increased due to interaction with QDs [75,91]. Visheratina et al [75] has shown that the effect of QDs on the chlorin e6 weakens with increase in size of CdSe QDs and with an increase in CdS shell thickness of CdSe/CdS QDs.…”
Section: Influence Of Qds On Optical Activity Of Chiral Moleculementioning
confidence: 98%
See 2 more Smart Citations
“…Optical activity can be induced in QDs by functionalization with chiral ligands via a relatively simple post-synthetic phase-transfer ligand exchange. ,, In this process, the initial hydrophobic ligands in QDs produced by the hot injection synthesis in organic medium are typically exchanged by chiral hydrophilic ligands, accompanied by the transfer of QDs into the aqueous phase. ,,, In this case, QDs exhibit optical activity in their absorption region, unlike the chiral ligand molecules, which typically absorb light only in the deep UV region. , The origin of induced chirality can be explained by the chiral distortion of QD surface atoms upon the adsorption of chiral ligands, ,,, or the hybridization of the energy levels of the QD and chiral ligand molecules leading to the splitting of QD hole–electron levels into two sublevels with different absorptions of circularly polarized light. ,,, …”
mentioning
confidence: 99%